Phytochemistry and Biological Activities of Amomum Species - Dinata, Deden Indra; Maharani, Rani; Muttaqin, Fauzan Zein; Supratman, Unang (Indonesian Journal of Chemistry, 2024)
Amomum is a pungent and aromatic plant genus that contains 150–180 species, where Southeast Asia is the center of endemism, with Indonesia indigenous to 24 breeds. These species are used as spices and traditional medicine for the treatment of various diseases. This paper aims to provide Amomum species summarized data regarding phytochemistry and biological activities. Several studies have been carried out on the fruits, seeds, roots, rhizomes, and leaves of Amomum species from 1999 to 2024, as approximately 127 metabolites were isolated as flavonoid, diterpenoid, diarylheptanoid, monoterpenoid, sesquiterpenoid, phenylpropanoid, phenolic, and steroid groups. Besides cytotoxicity, antioxidant, and anti-inflammatory potentials; it also has an owed tendency for use as a chemical marker. The extracts and compounds obtained from the Amomum species were evaluated for biological activities, including cytotoxicity, antioxidant, anticancer, antiproliferative, anti-inflammatory, antifungal, antimicrobial, neuroprotective, platelet antiaggregation, and antidiabetic properties. Tsaoko arilon (neolignane) had antiproliferative and cytotoxic activity, with the highest reactions considered as lead compounds for further development. The findings highlighted the significance of using compounds from the Amomum genus in traditional medicine and the discovery of new medicines. Therefore, the results supported the concept of utilizing Amomum species as a potential source for producing biologically active compounds.